MOLECULAR DYNAMIC SIMULATION OF THE POLYETHYLENE PYROLYSIS PROCESS - TETERIATNYKOV, HLIB; KARVATSKII, ANTON; IVANENKO, OLENA (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The aim of the study is to analyze the methods of simulating the polyethylene pyrolysis process using software. It is shown that molecular dynamics (MD) simulation methods have been widely used to study the pyrolysis process, which can be used to simulate reactive molecular systems with tens of thousands or more atoms with sufficient accuracy and in a reasonable time on modern personal computers. The stages of the MD simulation procedure and the main existing research directions are determined, including the assessment of the impact on increasing the selectivity of the yield of target products of such parameters as the type of pyrolysis reactors, temperature, process duration and the use of catalysts. Existing data indicate that the yield of target products at the level of 70% is provided by the optimal temperature of 500 °C, however, the yield of C2H4 and C3H6 is significantly reduced if the temperature exceeds 800 °C. The analysis of existing data has determined that detailed information on the formation and further use of olefin monomers, the role of radicals and the influence of heating conditions is still not clear for the optimal design of polymer pyrolysis reactors. Therefore, this opens up prospects for further research in this direction. As part of the analysis of methods for simulating the polyethylene pyrolysis process, polyethylene pyrolysis reactions using molecular dynamics methods using the ReaxFF force field and simulating the chemical reactions of the polyethylene pyrolysis process using LAMMPS were considered. It was concluded that molecular dynamics simulation using the ReaxFF reactive force field is a powerful tool for studying the pyrolysis process of polymers for the purpose of their utilization. The use of MD simulation makes it possible to detail the mechanisms of thermal destruction of polymers by constructing 2D and 3D structures of reactants and products, reaction kinetics and distribution of chemical reaction products.